Effects of LPS Composition in Escherichia coli on Antibacterial Activity and Bacterial Uptake of Antisense Peptide-PNA Conjugates - Goltermann, Lise; Zhang, Meiqin; Ebbensgaard, Anna Elisabeth; Fiodorovaite, Marija; Yavari, Niloofar; Løbner-Olesen, Anders; Nielsen, Peter E. (Frontiers in Microbiology, 2022)
The physical and chemical properties of the outer membrane of Gram-negative bacteria including Escherichia coli have significant impact on the antibacterial activity and uptake of antibiotics including antimicrobial peptides and antisense peptide-Peptide Nucleic Acid (PNA) conjugates. Using a defined subset of E. coli lipopolysaccharide (LPS) and envelope mutants, components of the LPS-core which provide differential susceptibility towards a panel of Bacterial Penetrating Peptide (BPP)-PNA conjugates were identified. Deleting the outer core of the LPS and perturbing the inner core only sensitized the bacteria towards (KFF)3K-PNA conjugates, but not towards conjugates carrying arginine-based BPPs. Interestingly, the chemical composition of the outer LPS core as such, rather than overall hydrophobicity or surface charge appears to determine the susceptibility to different peptide-PNA conjugates thereby clearly demonstrating the complexity and specificity of the interaction with the LPS/outer membrane. Notably, mutants with outer membrane changes conferring polymyxin resistance did not show resistance towards the BPP-PNA conjugates, thereby eliminating one possible route of resistance for these molecules. Finally, envelope weakening, through deletion of membrane proteins such as OmpA as well as some proteins previously identified as involved in cationic antimicrobial peptide uptake, did not significantly influence peptide-PNA conjugate activity.